Sound Absorption Coefficient Value test on Bagasse Fiber and Empty Palm Fruit Bunches as an Effective and Environmentally Friendly Sound Absorbing Composite Material Using a Simple Impedance Tube - Chandra Halim.M, S.Si (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Recently, the development and use of sound-producing tools is increasing and some people are annoyed by these sounds. Besides that, a sound suppressor was created to reduce the noise generated by sound-producing devices, one of which is a porous Absorber which is most widely used by the community because it is relatively light and cheap. Meanwhile, on the other hand, there are many natural fibers that generally cannot be utilized significantly, two of which are oil palm empty bunches and bagasse fibers which are hard and strong. Based on data from the Directorate General of Plantations at the Ministry of Agriculture, Indonesia's palm oil land area reached 14.23 million hectares (ha) with production reaching 48.68 million tons in 2018, this also has an impact on the number of empty palm fruit bunches. Palm empty bunches are a natural material that contains thick and coarse filaments so they can absorb sound. Meanwhile, Indonesia's sugarcane production reaches 34.9 million tons per year with an area of about 750,000 hectares (ha). The high productivity of sugarcane in Indonesia has resulted in many sugar cane processing factories which have resulted in a lot of bagasse as well. Bagasse has a carbon and silica content of about 90% and 10%, respectively. This carbon plays an important role in sound-absorbing materials because it is very suitable for converting energy waves into heat energy. The research method are literature study which used as the fundamental comprehension to do the bagasse fiber, empty palm fruit brunch and composite material research also an experimental method by making five types of panel samples. Variation will be tested at sound frequencies 400 Hz, 600 Hz, 800 Hz, 1000 Hz, and 1200 Hz.Â From all calculation, All variation works perfectly in range frequency 400 â€“ 600 Hz. For 800, 1000 and 1200 there are mines coefficient that informs the increasing of sound intensity level instead of reducing noises. The best variation is obtained by variation 1:1. It is proved by all coefficient of sound absorption is positive integer. The condition is totally opposite with control bagasse and variation 2:1. Both fibers have the ability to absorb the sound. All fibers work well if the composition is proportional and balance. The size of bagasse fiber are quite big compared to control empty palm fruit brunch. Therefore, control bagasse does not work well since the fibers are not stick densely. On the other hand, control empty palm fruit brunch has smooth fiber and bind each fiber easier rather than control bagasse. It can be proved by the value of coefficient of sound absorption for control empty palm fruit brunch is more positive than control bagasse. As the conclusion, variation 1:1 is the best variation for applying bagasse fiber and empty palm fruit brunch composite material. It also strongly proves that bagasse fiber and empty palm fruit brunch can be one of the material composite by applying variation 1:1 around of frequency 400-600 Hz.